PLASMA SURFACE MODIFICATION OF POLYETHYLENE TEREPHTALATE MEMBRANES - Трачевський, В.В.; Молозовенко, К.І.; Зінченко, М.В. (Proceedings of National Aviation University, 2012)
The influence of low-temperature plasma membrane surface of polyethylene terephtalate. The possibility of a polyethylene terephtalate membranes with the required surface properties.